Leadership’s Thinking Process with Contextual Intelligence in Executing Diversification Strategy - Scheepers, Caren B.; Maher, Camrin Roberts (Journal of Economics and Behavioral Studies, 2019)
Abstract: Diversification is a popular strategy for growth in response to a volatile economy. Current research, however, devotes little attention to the leadership required to ensure successful diversification, except for theoretical contributions on leaders’ thinking processes from scholars within the strategy discipline. This study thus conducted fieldwork in South African organisations to explore empirically how senior leaders’ thinking processes, demonstrating contextual intelligence, contributing to successful diversification. A qualitative study was conducted by collecting data through semi-structured interviews from 15 executives with an average of 21 years’ experience in senior management roles, who had been involved in diversification in South Africa. A critical incident interview technique was used, and interviewees offered examples of how they changed their way of thinking in creating an environment for successful diversification. The analysis revealed that continuous change was required to successfully implement a diversification strategy. Leaders demonstrated specific thinking processes, for example: being intently aware of their context, they filtered and compared this information to their schema or preconceived cognitive representations. In case of a mismatch, they changed their way of thinking; and directed contextual information to challenge others’ current way of thinking. Surprising findings included leaders’ sensing other’s emotions and appealing to these through storytelling to elicit support for their diversification. Diversification requires organisations to invest in developing the agility and global perspective of leadership to increase awareness of trends in their context, their own biases and to shift their mindsets as well as purposefully challenging other’s thinking.